2019
DOI: 10.1152/japplphysiol.00056.2019
|View full text |Cite
|
Sign up to set email alerts
|

Heavy upright exercise increases ventilation-perfusion mismatch in the basal lung: indirect evidence for interstitial pulmonary edema

Abstract: Ventilation-perfusion (V̇a/Q̇) mismatch during exercise may result from interstitial pulmonary edema if increased pulmonary vascular pressure causes fluid efflux into the interstitium. If present, the increased fluid may compress small airways or blood vessels, disrupting V̇a/Q̇ matching, but this is unproven. We hypothesized that V̇a/Q̇ mismatch would be greatest in basal lung following heavy upright exercise, consistent with hydrostatic forces favoring edema accumulation in the gravitationally dependent lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Other MRI data reported increased ventilation-perfusion mismatch only in the basal lung of athletes following 45 min of cycling exercise, consistent with the development of lung edema in the gravitationally dependent lung during heavy exercise (Tedjasaputra et al 2019 ).…”
Section: Data After Exercisesupporting
confidence: 65%
See 1 more Smart Citation
“…Other MRI data reported increased ventilation-perfusion mismatch only in the basal lung of athletes following 45 min of cycling exercise, consistent with the development of lung edema in the gravitationally dependent lung during heavy exercise (Tedjasaputra et al 2019 ).…”
Section: Data After Exercisesupporting
confidence: 65%
“…Log standard deviation of perfusion and ventilation distributions (Log SDQ, and log SDv, respectively) were correlated with the increase in ΔA-aO 2 and diffusion limitation (Hopkins et al 1998a ; Hopkins 2005 , 2020 ). More recent data confirm that 45 min at about 80% increased mismatch in the basal lung after exercise, likely reflecting gravitationally dependent interstitial pulmonary edema (Tedjasaputra et al 2019 ).…”
Section: Data That Are Consistent With But Not Proof Of Interstitial ...mentioning
confidence: 76%
“…In addition, studies have shown that the increased venous return in the supine position is conducive to increasing the fluid shift to the pulmonary circulation and interstitium. This may compress small airways and/or blood vessels, unbalancing the overall pulmonary V/Q ratio and reducing ventilatory efficiency ( 52 ). Bryan et al ( 5 ) demonstrated that the change from an upright position to the supine position in healthy individuals results in a decrease in the V/Q of the entire lung from 0.83 to 0.76.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no established protocols yet for this specific pathology, these patients benefit from verticalization training with oxygen therapy and a respiratory rehabilitation program which includes learning breathing techniques, resistance training, and physical reconditioning. Initial exercises should be of low to moderate intensity in order not to exacerbate the areas of ventilation-perfusion mismatch [8] . Despite causing apprehension in patients and in their health professionals, it is a reversible condition, with symptomatic resolution expected in 6-39 days [4] .…”
Section: Discussionmentioning
confidence: 99%